Real estate dispossession, income and immigration in Las Palmas de Gran Canaria (Spain) - Juan Manuel Parreño Castellano; Josefina Domínguez-Mujica; Claudio Moreno-Medina (Boletín de la Asociación de Geógrafos Españoles)
The legal proceedings of real estate dispossession are essential elements in understanding the impact of the economic crisis on Spanish cities. Those that took place between 2009 and 2017 in Las Palmas de Gran Canaria, their quantitative dimension and their intra-urban distribution are analysed in this study. This perspective allows an appreciation of their relationship with the unequal distribution of income and alien status, factors leading the investigations on the loss of property. In order to achieve this objective, the records of the Common Service of Notifications and Seizures have been used together with data of the Inland Revenue Ministry and Municipal Register, combining statistical and cartographical analysis with the purpose of finding associations and predictive factors. The study reveals that there is a great concentration of real estate deprivation in the central areas of the city and that the standards of distribution of dispossession are inversely related to the level of income of the urban districts and directly related to the foreign population. This tends to confirm that dispossession must be interpreted as the result of mechanisms of capitalist accumulation, which reinforce socio-urban inequalities.